1998
DOI: 10.1029/98jb00606
|View full text |Cite
|
Sign up to set email alerts
|

Some physical requirements for the emplacement of long basaltic lava flows

Abstract: Abstract. Long basaltic lava flows (over 100 km in length) require specific emplacement conditions to prevent the lava from freezing as it is transported to the flow front. The minimum dimensions of the lava transport systems (tubes, channels, or sheets) require that the flow have a volume greater than several cubic kilometers. Long lava flows are emplaced on slopes less than 10% (•-5 ø) and the lava being transported must cool at a rate less than 0.5øC/km. We show that there are two modes by which thermally e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
175
2
4

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 210 publications
(190 citation statements)
references
References 77 publications
9
175
2
4
Order By: Relevance
“…We note that the value of Re marking the transition to turbulent flow depends on both the exact version of the Reynolds number used and the geometry of the flow. The various permutations of Re and the critical Re that permeate the published literature were discussed by Keszthelyi and Self[1998b]. In this paper we use Re = p rh <v> / rl,…”
Section: Several Points Inmentioning
confidence: 99%
“…We note that the value of Re marking the transition to turbulent flow depends on both the exact version of the Reynolds number used and the geometry of the flow. The various permutations of Re and the critical Re that permeate the published literature were discussed by Keszthelyi and Self[1998b]. In this paper we use Re = p rh <v> / rl,…”
Section: Several Points Inmentioning
confidence: 99%
“…Massive eruptions are deduced mainly from the size of plateau edifices coupled with inferred short eruption periods (Coffin and Eldholm, 1994). In addition, it is suggested that low oceanic plateau flank slopes imply high eruption rates and long flows similar to continental flood basalts (Keszthelyi and Self, 1998;Sager et al, 1999). Ocean Drilling Program (ODP) cruises have sampled the largest oceanic plateaus, Kerguelen (Leg 183; Coffin et al, 2002) and Ontong Java (Leg 192;Mahoney et al, 2001), and they have found that massive lava flows are common.…”
Section: Introductionmentioning
confidence: 99%
“…Holocene obsidian flows in the western US preserve evidence of a cooled surface crust in folding, crease structures and large gas cavities (Fink 1980a;Anderson and Fink 1989;Castro and Cashman 1999;Castro et al 2002;Lescinsky and Merle 2005). Crustal development increases the strength of the flow (Hon et al 1994;Griffiths and Fink 1997;Griffiths 2000;Lyman et al 2005), insulates the flow and reduces heat loss (Swanson 1973;Fink and Griffiths 1998;Keszthelyi and Self 1998;Harris and Rowland 2009;Tuffen et al 2013). When the crust fractures during lava movement, blocky lava is formed (Finch 1933;Macdonald 1953;Fink 1980a;Harris et al 2017), defined as being made up on distinct blocks without some of the key characteristics of an 'a'a flow, such as a spiny or clinker surface (Finch 1933).…”
Section: Crust Formationmentioning
confidence: 99%
“…For instance, the development of a cooled surface crust promotes crustal folding during flow advance (Fink 1980a;Castro and Cashman 1999) and crease structure development (Anderson and Fink 1992;Lescinsky and Merle 2005). Crusts influence lava flow growth (Griffiths and Fink 1992;Fink and Griffiths 1998), and thermally insulate the flow, facilitating prolonged mobility and advance (Swanson 1973;Manley 1992;Fink and Griffiths 1998;Keszthelyi and Self 1998;Harris and Rowland 2009;Tuffen et al 2013). This has been previously observed in dacitic lava flow emplacement at Santiaguito (Harris et al 2002(Harris et al , 2004, and active rhyolitic flow emplacement at Puyehue-Cordón Caulle Magnall et al 2017).…”
Section: Introductionmentioning
confidence: 99%